PENGAWASAN PELAKSANAAN PENDIDIKAN AGAMA ISLAM PADA SEKOLAH UMUM DAN MADRASAH: STUDI KASUS DI KABUPATEN ACEH TAMIANG DAN KOTA LANGSA, PROVINSI ACEH - Ismail Ismail (Majelis Pendidikan Aceh, 2022)
Islamic religious lesson is a very important lesson in the formation of students with noble character, faith and devotion to Allah SWT. However, currently a number of teenagers in Aceh are experiencing a moral crisis, do not have an Islamic character and do not practice Islam kaffah. This is certainly related to the implementation of Islamic religious lesson called PAI in schools/madrasahs. In this regard, a study has been conducted to examine the supervision of PAI in schools/madrasahs in Aceh Tamiang district and Langsa City. The method used was qualitative, respondents were from schools/madrasahs, supervisors, Education Department and the Ministry of Religion. The results of this work show that the quality of the supervisory recruitment process needs to be improved; the number of supervisors needs to be increased; the ability of supervisors need to be strengthened. In addition, it is essential to improve facilities and infrastructure to support the learning process of PAI and strengthening of Islamic religious education teachers. The competence of PAI teachers can be improved by increasing the role of supervisors.